2022
DOI: 10.1371/journal.pone.0274642
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early pregnancy anemia in rural Sri Lanka: Does being ‘under care’ iron out socioeconomic disparities?

Abstract: Globally, more than a third of pregnant women are anemic, and progress in its prevention and control is slow. Sri Lanka is a lower-middle-income country with a unique public health infrastructure that provides multiple interventions across the lifecycle for anemia prevention, despite which anemia in pregnancy remains a challenge. Studying the factors associated with maternal anemia in this context would provide unique information on challenges and opportunities encountered as low-and-middle-income countries at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
0
0
2
Order By: Relevance
“…This may be because coming from wealthier households could also mean that women also access better health services and healthier, su cient food than their counterparts with less income. This agrees with results from several studies conducted in Tanzania, Sri Lanka, Nigeria, Rwanda, Uganda and Ethiopia which found women with low wealth index being more likely to be anaemic [27,[40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 92%
“…This may be because coming from wealthier households could also mean that women also access better health services and healthier, su cient food than their counterparts with less income. This agrees with results from several studies conducted in Tanzania, Sri Lanka, Nigeria, Rwanda, Uganda and Ethiopia which found women with low wealth index being more likely to be anaemic [27,[40][41][42][43][44].…”
Section: Discussionsupporting
confidence: 92%
“…Penyebab kurangnya gizi selama kehamilan kemungkinan karena beberapa faktor diantaranya mual dan muntah, infeksi kronis atau depresi, penggunaan obat tertentu yang bisa mengganggu penyerapan nutrisi sehingga asupan gizi dan kalori yang tidak memadai. (Amarasinghe et al, 2022) Pemenuhan nutrisi/gizi yang tepat sangat membantu tumbuh kembang janin dalam kandungan.…”
Section: Pendahuluanunclassified
“…Ibu hamil yang memiliki IMT yang rendah berhubungan signifikan dengan kejadian anemia selama kehamilan (Millatina et al, 2020). Sedangkan menurut penelitian yang dilakukan di Sri Langka, ibu hamil yang underweight berisiko 1,6 kali lebih besar terkena anemia dibandingkan ibu hamil dengan BMI normal, overweight, atau obesitas (Amarasinghe et al, 2022).…”
Section: Underweightunclassified